0985 Differences in the Timing of Melatonin Secretion between African American and Caucasian Patients with Major Depressive Disorder. (27th April 2018) - Polymeropoulos, C; Hull, J T; Xiao, C; Polymeropoulos, M H
Abstract: Introduction: Circadian physiology has been hypothesized to play a role in the etiology of Major Depression and may affect symptom expression and response to treatment. We have studied markers of circadian physiology in a large cohort of patients with MDD and have identified differences of the expression of the circadian timing system between African Americans and Caucasians. Methods: Patients diagnosed with MDD (DSM-IV), including 94 African Americans (70 female) ages 19–61 years (mean + SD = 41.0 ± 11.7 years) and 235 Caucasians (158 female) ages 18–65 years (42.9 ± 13.5 years) participated in this study. Patients collected saliva samples at home every hour for 9 hours starting 5 hours prior to their habitual bedtime. Participants recorded date and clock time of each sample and were instructed to avoid bright light and wear amber-lens (blue-light filtering) goggles throughout collection. Samples were frozen until assayed for melatonin. Melatonin onset (MO) was defined as the interpolated clock time between 2 consecutive samples when melatonin concentrations rose above 4 pg/mL. The sample clock times for collections performed during daylight saving time were not adjusted (-1 hour) to standard time. A paired Student′s t-test was used to analyze the data. Results: The mean Melatonin onset (MO) clock time was at 9:04 PM in the African American-MDD population as compared to 9:35 PM in the Caucasian-MDD population. The difference of 31 minutes between the two populations was statistically significant (pvalue =0.0229). Conclusion: The timing of melatonin secretion in an African American-MDD population occurred at an earlier time relative to the Caucasian-MDD population. The role of this observation in the pathophysiology and treatment of MDD would need to be further investigated. Support (If Any): This work was supported by Vanda Pharmaceuticals Inc.